KEDUDUKAN FIDUSIA SEBAGAI JAMINAN AKAD PEMBIAYAAN MURABAHAH PADA BANK SYARIAH: STUDI KASUS PADA BPRS BHAKTI SUMEKAR SUMENEP - Halimatus Sadiyah (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2018)
Bank Syariah with the all products and services in running its business generally also guides to the banking provisions and other provisions as well, such as agreement of fiduciary warranties that arranged by the constitution of the republic of indonesia No 42 of 1999. It was abaut fiduciary guarantee (UUJF), financial murabahah is one of the enough-developed in Bank Syariah. Therefore, in its bonding, financial murabahah often uses fiduciary because its loading considered simple enough, relatively fast, and easy.This study aims to find out how the practical development of financial murabahah by using fiduciary guarantee from 2015 to 2016 in Bhakti Sumekar BPRS of Sumenep, and it also aims to find out  how islamic perspective about fiduciary guarantee.The result of this study reveals that the practical development of financing murabahah in using fiduciary guarantee from 2015 to 2016 was increasing because it was from side offer of Bank Syariah. Accordingly, financial murabahah is rated to have minimum risk than type of financial profit sharing.